Functions with bounded E-d-variation on undirected tree networks - Marian, Daniela (Rev. Anal. Numér. Théor. Approx., 2002)
In this paper we define and study functions with bounded \(E-d\)-variation on undirected tree networks. For these functions with bounded \(E-d\)-variation we establish a Jordan type theorem. We adopt the definition of network as metric space introduced by P. M. Dearing and R. L. Francis (1974).